Psychometric Evaluation of the Kidney Disease Quality of Life 36-Item Survey Instrument (KDQOL-36): A Comparison Between Older and Younger Adults Receiving Dialysis - Hall, MD, MBA, MHSc, Rasheeda; Luciano, PhD, Alison; Pieper, DPH, Carl; Colon-Emeric MD, MHSc, Cathleen (The Journal of Nephrology Social Work, 2018)
Medicare requires that dialysis units assess quality of life in all patients annually using the Kidney Disease Quality of Life 36-item survey instrument (KDQOL-36). However, whether the KDQOL-36 is a valid instrument for older adults receiving dialysis is not known. The objective of this study was to evaluate the reliability and validity of the KDQOL-36 in both older and younger patients receiving dialysis. We used KDQOL-36 item responses from a nationally representative sample of 3500 older (≥ 75 years) and 500 younger (ages 21 to 74 years) patients receiving dialysis in 2012. We assessed subscale means, ceiling/floor effects, internal consistency reliability, and construct validity. Results demonstrated that the KDQOL-36 has comparable reliability and validity in older and younger adults receiving dialysis.